Simulations of V-I characteristics in a plasma-focus gun - Tou, T.Y.; Chin, Oi Hoong; Chen, Y.H. (Institute of Electrical and Electronics Engineers (IEEE), 1992)
The voltage (V) and current (I) characteristics in a plasma focus gun are simulated to yield the current efficiency and the rundown velocity of the current sheath. Since the discharge circuit is strongly influenced by the rundown dynamics of the current sheath, the simple snowplow model, which is modified to include the time-varying current and mass efficiencies, f and k, respectively, is employed. The computer simulations are carried out for two separate experiments using deuterium and argon gas. A steady state of constant rundown velocity and saturated sheath current for both gases is correlated to the maximum holding voltage of the glass insulator. As much as 27 of the total discharge current for the deuterium gas and 33 for argon gas stay behind as leakage currents around the glass insulator when the radial compression phase begins.